Comparative Study of Temporalis Fascia Graft versus Cartilage Shield Tympanoplasty in Chronic Otitis Media - Mucosal Type - Shrestha, Kumar; Paduel, Dhundi Raj; Bhandari, Shama; Mahaseth, Subhash Chandra (Journal of Nepalgunj Medical College, 2022)
Introduction: Tympanoplasty is the procedure of choice for surgical correction of tympanic membrane perforation triggered by either chronic otitis media or trauma. Various types of autologous grafts have been used to close tympanic membrane perforations among which temporalis fascia and tragal cartilage are preferred, due to their anatomic proximity, ease of harvesting and suppleness. Aims: To compare clinical and audiological outcomes of type 1 tympanoplasty where temporalis fascia and tragal cartilage were used as the graft material. Methods: A prospective study was conducted on 50 patients of ages ranging from 10 to 50 years with Chronic Otitis Media - Mucosal. All the patients underwent type 1 tympanoplasty and were categorized into Group-A (Temporalis fascia graft) and Group-B (Cartilage graft), each group comprising of 25 patients. Graft uptake rate, hearing gain and air bone gap closure were compared between the groups in 4 and 8 weeks after surgery. Results: Out of total 50 patients, 20 were male and 30 were female. The average age of the patients was 28.20 years. The total hearing gain in the whole series was 14.94 dB while the total air bone gap closure was 14.78 dB respectively. The difference between pre and post-operative hearing was statistically significant for both air bone gap and air conduction, (P<0.05) in the whole series. There was 15.56 dB improvement in mean hearing threshold and 15.64 dB mean air bone gap closure in the fascia group, compared to 14.32 dB improvement in mean hearing and 13.92 dB mean air bone gap closure in the cartilage group. Graft uptake rate in the temporalis fascia group was 84% and the cartilage group was 92 % with significant difference in the graft uptake rate between the groups. Conclusion: The graft uptake rate and hearing results of tragal cartilage are comparable to those of temporalis fascia. Cartilage tympanoplasty has a higher graft uptake rate with low failure rate and also shows a high degree of reliability in high risk cases. Both cartilage and fascia tympanoplasty provided similar improvements in the hearing outcome post-operatively. Thus, cartilage tympanoplasty is recommended as an alternative option.